Development of electro-hydro autonomous parking braking system for electric vehicle - Rahman, Mohammed Ataur; Sany, Ihsan (Book Publisher International, 2020)
The importance of the parking braking system is to ensure the vehicle braking at parking in any road to minimize the human effort and increase the safety of the vehicle. The automatic parking braking system (APBS) has been developed in such a way that it activates automatically as long as vehicle ignition-switch turn off and door open. APBS offers distinct advantages for new-car are easier to operate, additional safety features compared to conventional parking brakes, braking automatically on hill in parking with safety, less space, improve interior ergonomics, and reduce vehicle weight and cost. APBS replaces large manually operated levers or foot pedals with a small activation switch located on a vehicle’s center console. Conventional parking brake system requires the driver to manually pull the lever if the brakes are to be applied. To some extent, the vehicle is left without applying the parking brake due to the insensibility, which could make the vehicle in danger if there any gradient of the road and strong wind. The aim of this study is to present an automatic electro-hydro parking braking system to park the vehicle on the road with additional safety. Associating the wheel speed sensors (WSS), Accelerator off-sensors (AoS), Alder Magnetic Sensor (AMS), controller, and an actuator develop this with linear displacement mechanism. This electro-hydro automatic parking braking system automatically brakes the vehicle when it parks. It ensures the vehicle to remain stationary when it is parked and prevents vehicle rollaway or any unwanted movement that might occur. It increases the safety of the vehicle as well as others around it. The actuator linear mechanism displacement is controlled by the auto-clamping system when the vehicle park based on the response of the WSS, AMS , and AoS. The model has been tested considering the road gradient 2-25%. The automatic parking braking system requires hydraulic pressure 383.66 kPa to ensure the vehicle park on 25% gradient, which is 11% less than the vehicle to brake from speed of 35 km/h.